COMPETENCY ANALYSIS OF AUDITORS WHO HAVE RELATIVES WITH PARTNERS IN PRODUCING QUALITY AUDITS AT PUBLIC ACCOUNTING FIRMS IN BANDUNG - Wawan Asad Sutrisna; Tina Merlina; Apriyanti Apriyanti (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2023)
Kinship relations are a homework in itself for business actors in developing countries to obtain competent workers. The aim of this research is to determine the competency of an auditor who has a relative relationship with a partner in producing quality audits. This research uses a qualitative method with an ethnomethodological approach in one of the local KAPs in the city of Bandung. It is concluded that competence influences the quality of audits at Public Accounting Firms (KAP) in the Bandung area. With a very strong and positive correlation category, which means that the better the audit competency, the better the audit quality.